Simulation Recording of an ECG, PCG, and PPG for Feature Extractions - Al-Qazzaz, Noor Kamal; Abdulazez, Israa F.; Ridha, Salma A. (Al-Khwarizmi Engineering Journal, 2014)
Recently, the development of the field of biomedical engineering has led to a renewed interest in detection of several events. In this paper a new approach used to detect specific parameter and relations between three biomedical signals that used in clinical diagnosis. These include the phonocardiography (PCG), electrocardiography (ECG) and photoplethysmography (PPG) or sometimes it called the carotid pulse related to the position of electrode.Comparisons between three cases (two normal cases and one abnormal case) are used to indicate the delay that may occurred due to the deficiency of the cardiac muscle or valve in an abnormal case.The results shown that S1 and S2, first and second sound of the heart respectively, can be determined from another signal like ECG. Moreover, the position of QRS complex and the end of T wave could be estimated by using PPG signal.